Determinación del índice de calidad del agua del meandro abandonado en Moronillo mediante parámetros físicos químicos y bioindicadores Iquitos - Perú 2021 - Lay Ríos, Tania (2024)
The water quality index of the abandoned meander in Moronillo (Rio Nanay) was determined through the evaluation of its physical-chemical parameters and bioindicators. Water samples were obtained at three different stations: one near the Faculty of Medicine, another near the Trujillo Street bridge and another near the PTAR. The results of the physical and chemical analyzes demonstrate that the water does not present acceptable standards for human consumption. The microbiological analysis revealed the presence of high levels of total coliforms (1,167 NMP/100ml, 2,660 NMP/100ml and 782 NMP/100ml) and thermotolerant coliforms (70,437 NMP/100ml, 2,203 NMP/100ml and 4,037 NMP/100ml), which indicates high fecal contamination in the water. Furthermore, the presence of a large number of emerging and floating plants suggests that the water source is experiencing eutrophication and loss of the water surface. In conclusion, the high levels of sulfur, nitrogen and detergent oxides, as well as the physical and chemical changes observed, reveal that this abandoned oxbow ecosystem is highly contaminated. The water quality index confirms this high contamination, and by combining all these factors, a value is obtained that clearly indicates the precarious ecological and biological situation of the area, represented by an orange color.